The Elephant in the Classroom: Using YouTube Comments to Address the Essential but Unacknowledged Topic of Race - Riley, Jacqueline; Slay, Laura E.; Revelle, Carol (International Journal of Multicultural Education, 2021)
Drawing on critical race media theory, this praxis article describes how instructors can effectively introduce critical race literacy theory in a teacher education class using online videos. Ultimately, this study helps us to better understand how viewing YouTube videos and responding critically to YouTube user comments can help preservice teachers acknowledge and challenge their pre-existing beliefs related to teachers and students of color in a teacher education writing course. Data analysis reveals that preservice teachers’ idealism for compassionate teaching is embedded in a superficial understanding of sociocultural differences and lacks an understanding of how race affects student learning.